Industrial Development, Subsidy Reform and Export Behaviour : An Evidence from ASEAN-5 Economies - Dzul Hadzwan, Bin Husaini; Shazali, Bin Abu Mansor; Bakri, Bin Abdul Karim; Chin, Hong Puah; Kueh, Jerome Swee Hui; Lau, Evan Poh Hock (Universiti Putra Malaysia Press, 2019)
This study explores the impact of subsidy reform on export performance in ASEAN-5 economies, whereby the output of this research may be useful for the policymakers to balance favourable subsidy reform upon sustainable economic development while controlling fiscal burden. The objective of this study is to explore the impact of subsidy reform on export growth while considering an exchange rate and the industrial value added as a control variable. This study covers a panel data of ASEAN-5 economies from the 1992 to 2015. The dynamic panel data analysis was employed to evaluate the magnitude impact of subsidy expenditure by the government, exchange rate and industrial value added on export performance. The Pooled Mean Group (PMG) model was employed to determine the long run coefficient in the model. The finding concluded that: 1) Export growth was expected to increase as the subsidy growth increases, 2) currency appreciation was expected to encourage export growth and 3) Industrial development would increase export growth as many outputs can be produced in a period of time. As an absence of subsidy would lead to a lost in export, and the government is recommended to implement an adequate offset policy to cushion any negative impact reflected by the absence of a subsidy in an economy.